The The Effect of Picture Word Card Media on Early Reading Ability of Children at Teratai Kindergarten, State University of Makassar - Khansa, Andi aqiilah; Muhammad Yusri Bachtiar; Herman, Herman (CV. Creative Tugu Pena, 2025)
This study employed a quasi-experimental design aimed at examining the effect of using picture word card media on children’s early reading skills at Teratai Kindergarten, State University of Makassar. The research specifically focused on comparing children’s reading abilities before and after the treatment, as well as evaluating the significant impact of the media on Group B students. The independent variable in this study was the use of picture word cards, while the dependent variable was children’s early reading ability. The study involved a total population of 49 children, with 10 selected as samples through purposive sampling—5 in the experimental group and 5 in the control group. Data were analyzed using descriptive statistics and non-parametric tests. The findings revealed that the use of picture word card media had a significant effect on improving early reading ability among young children at Teratai Kindergarten, UNM.